ALVIN PLANTINGA’S REFORMED EPISTEMOLOGY - MUSTAȚĂ, Gabriel (Studia Universitatis Babeș-Bolyai Philosophia, 2020)
Alvin Plantinga’s Reformed Epistemology. Alvin Plantinga is a well-known defender of Reformed epistemology. The main thesis of the Reformed epistemology argues that faith in God is rational and justified without the aid of arguments or evidence. In this paper, we intend to describe Alvin Plantinga’s perspective, more precisely, the A / C model (Aquinas / Calvin) proposed by him, in which faith in God is innate and does not need arguments or evidence, and then to analyze the objections on this model, in order to determine whether faith in God can be considered basic.